2015
DOI: 10.1038/ncomms7173
|View full text |Cite
|
Sign up to set email alerts
|

Coherent spin control of a nanocavity-enhanced qubit in diamond

Abstract: A central aim of quantum information processing is the efficient entanglement of multiple stationary quantum memories via photons. Among solid-state systems, the nitrogen-vacancy centre in diamond has emerged as an excellent optically addressable memory with second-scale electron spin coherence times. Recently, quantum entanglement and teleportation have been shown between two nitrogen-vacancy memories, but scaling to larger networks requires more efficient spin-photon interfaces such as optical resonators.Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
198
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(201 citation statements)
references
References 45 publications
2
198
0
Order By: Relevance
“…This technique is commonly used and can typically reversibly redshift cavity modes by at least 20 nm without degrading their Qs (17,18,22,29). Modes can also be appropriately blueshifted of the ZPL by using previously reported techniques for tuning 4H-SiC cavities (25).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…This technique is commonly used and can typically reversibly redshift cavity modes by at least 20 nm without degrading their Qs (17,18,22,29). Modes can also be appropriately blueshifted of the ZPL by using previously reported techniques for tuning 4H-SiC cavities (25).…”
Section: Significancementioning
confidence: 99%
“…The Purcell enhancement can be calculated from lifetime measurements using the following relation (16,29,30):…”
Section: Significancementioning
confidence: 99%
“…In the visible region, Q-values tend to be much lower even for ring resonators, and, in this spectral region 1D-PHC cavities maximum Q is 24 000. The maximum coupling of single NV with a 1D-PHC is achieved with a Q = 9900 with a loaded Q = 3000 when strongly coupled to NV 51 , while it appears that the best performance in the direction to operate non-linear quantum optics and integrated optical quantum networks is achieved by entangling SiV color centers in diamond 1D nano-cavities 68 . A combination of these advances has led to optomechanical devices in diamond, and we can foresee novel applications in spin optomechanics where optical and mechanical modes are coupled in the same devices with spin defects; additionally spin control can be achieved in diamond crystals by photonics approach at the expenses of operating at cryogenic temperature.…”
Section: Discussionmentioning
confidence: 99%
“…51 it is reported that the highest F SE = 62 is achieved for a single NV in a 1D-PHC cavity with a measured Q~9900 and V~1.05 · (λ/n) 3 ( Figure 7). A linear increase of the lattice constant from 0.9 · a to a in increments of 0.02 · a per period away from the center, defines the cavity defect state.…”
Section: Phc Cavitiesmentioning
confidence: 99%
“…For quantum information, in contrast, these systems are promising as they potentially form a coherent interface between spins and photons in quantum networks [89]. In our case, waveguide-like structures that channel the NV's broad emission into certain spatial modes and direct the light towards the collection optics (nanopillars; see Figure 5b) seem more suitable mainly due to their broadband operation.…”
Section: Nanostructures For Photonics and Scanning Probe Operationmentioning
confidence: 99%